'It's a traumatic illness, traumatic to witness': a qualitative study of the experiences of bereaved family caregivers of patients with cutaneous T‐cell lymphoma. (1st October 2018) - Orlowska, D.; Selman, L.E.; Beynon, T.; Radcliffe, E.; Whittaker, S.; Child, F.; Harding, R.
Summary: Background: Cutaneous T‐cell lymphomas (CTCL) are rare cancers, which can be difficult to diagnose, are incurable and adversely affect quality of life, particularly in advanced disease. Families often provide care, but little is known about their experiences or needs while caring for their relative with advanced disease or in bereavement. Objectives: To explore the experiences of bereaved family caregivers of patients with CTCL. Methods: Single, semi‐structured qualitative interviews were conducted with bereaved family caregivers of patients with CTCL recruited via a supra‐regional CTCL clinic. Transcribed interviews were analysed thematically, focusing on advanced disease, the approach of death and bereavement. Results: Fifteen carers of 11 deceased patients participated. Experiences clustered under four themes: (1) complexity of care and medical intervention; (2) caregiver roles in advanced CTCL; (3) person‐centred vs. organization‐centred care in advanced CTCL and (4) knowing and not knowing: reflections on dying, death and bereavement. Caregivers often had vivid recollections of the challenges of caring for their relative with advanced CTCL and some took on quasi‐professional roles as a result. Advanced disease made high demands on both organizational flexibility and family resources. For many caregivers, seeing disease progression was a prolonged and profoundly traumatic experience. The extent to which they were prepared for their relative's death and supported in bereavement was highly variable. Sub‐themes within each theme provide more detail about caregiver experiences. Conclusions: Family caregivers should be considered part of the wider healthcare team, acknowledging their multiple roles and the challenges they encounter in looking after their relative with CTCL as the disease progresses. Their experiences highlight the importance of organizational flexibility and of good communication between healthcare providers in advanced CTCL.